VD_FINDINFO Décision / 2013 / 500 vom 22. März 2013 - VD Tribunal cantonal (2013)
GARDIEN DE PRISON, ILLICÉITÉ, ABUS D'AUTORITÉ, LÉSION CORPORELLE SIMPLE, AGRESSION | 14 CP, 319 CPP (CH), 393 al. 1 let. a CPP (CH)